2022
DOI: 10.1021/acs.langmuir.1c02617
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Drag Reduction by Magnetic Confinement

Abstract: The frictional forces of a viscous liquid flow are a major energy loss issue and severely limit microfluidics practical use. Reducing this drag by more than a few tens of percent remain elusive. Here, we show how cylindrical liquid−in−liquid flow leads to drag reduction of 60−99% for sub-mm and mm-sized channels, regardless of whether the viscosity of the transported liquid is larger or smaller than that of the confining one. In contrast to lubrication or sheath flow, we do not require a continuous flow of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…156 The idea of magnetic fluid DR is as follows: under the action of the external magnetic field, the magnetic fluid is attached to the inner wall of the pipe, and the flexible boundary interface is used to replace the rigid boundary interface, which makes the boundary surface fluctuate synchronously with the flow of the fluid, resulting in the change of velocity distribution in the laminar boundary layer. 154 When the velocity on the surface of the boundary layer is greater than zero, the velocity gradient on the boundary surface decreases, thus reducing the shear force on the boundary surface and the energy consumed by the shear force, to achieve the purpose of DR. Sun et al 157 built a set of experimental facilities based on drag reduction of magnetic fluid consisting of a liquid container, magnets, a plexiglass pipe with a length of 800 mm and an inner diameter of 40 mm. Nd−Fe−B magnet is used to generate an external magnetic field outside the pipeline, and the experimental fluid is silicon oil.…”
Section: Magnetic Nanofluid Drag Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…156 The idea of magnetic fluid DR is as follows: under the action of the external magnetic field, the magnetic fluid is attached to the inner wall of the pipe, and the flexible boundary interface is used to replace the rigid boundary interface, which makes the boundary surface fluctuate synchronously with the flow of the fluid, resulting in the change of velocity distribution in the laminar boundary layer. 154 When the velocity on the surface of the boundary layer is greater than zero, the velocity gradient on the boundary surface decreases, thus reducing the shear force on the boundary surface and the energy consumed by the shear force, to achieve the purpose of DR. Sun et al 157 built a set of experimental facilities based on drag reduction of magnetic fluid consisting of a liquid container, magnets, a plexiglass pipe with a length of 800 mm and an inner diameter of 40 mm. Nd−Fe−B magnet is used to generate an external magnetic field outside the pipeline, and the experimental fluid is silicon oil.…”
Section: Magnetic Nanofluid Drag Reductionmentioning
confidence: 99%
“…152 Dunne et al 153 pointed out that the use of magnetic fluid can create an almost frictionless liquid−liquid channel in which water flows in the center of the pipe and avoids direct contact with the solid wall (see Figure 18). Dev et al 154 reported that the drag of ferromagnetic fluid in a microchannel (submillimeter or millimeter) liquid flow is reduced by 60% to 99%, and the process is not affected by the viscosity of the transported liquid, which means that this technology is suitable for both light and heavy oil. At present, magnetic fluid has been successfully prepared under laboratory conditions, which has been widely utilized in the fields of machinery, aerospace DR, and has potential application value in the fields of medicine, chemical industry, fluid transport and other fields.…”
Section: Magnetic Nanofluid Drag Reductionmentioning
confidence: 99%
“…Reduction of fluid resistance is of significance to increasingly emerging energy and environmental issues. Turbulence is the major source of fluid resistance in many cases and has attracted extensive attention. Hence, research into drag reduction has focused on methods to depress turbulence near walls. Biomimetic riblet surfaces, such as blade, wavy, sinusoidal, and herringbone riblet (Blade, Wavy, Sinusoidal, and Herringbone, respectively) surfaces, inspired by sharks and birds have achieved significant reductions in turbulent drag reduction. Blade surfaces have been proven to provide obvious drag reduction, and they have shown promise for many potential applications in the pipeline, aircraft, energy, and transportation industries. , …”
Section: Introductionmentioning
confidence: 99%